DETERMINATION OF IDENTITY AND ADEQUATE QUALITY OF GATHERINGS OF NL INTERNATIONAL ENERWOOD EVERY COMPANY - S. P. Lukashuk; G. G. Nemashkalova; Yu. N. Malysheva (Фармация и фармакология (Пятигорск), 2015)
NL International Enerwood Every company produces tea products like “Women’s health tea”, “Health kidneys tea”, “Health joints tea”, “Teatime for longevity”, “Vitamine tea”, “Strong liver tea”, “Strong heart tea”, “Soothing tea”, “Clear lungs tea”. We focused on “Healthy kidneys tea” and “Teatime for longevity”. This article presents the results of morphological and anatomical and quality analysis of the tea components.